PENGARUH PENERAPAN MODEL EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR TEMATIK KELAS IV SEKOLAH DASAR - Sri Nuryanti; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this study is to describe the effect of applying the example non example model on the thematic learning outcomes of Grade IV students. The method used is an experimental method in the form of Quasi Experimental Design with Non Equivalent Control Group Design experimental design. The population which is at the same time a sample in this study is grade IV students namely IV A and IV B. The data collection technique used is the measurement technique. Data collection tool in the form of a written test in the form of multiple choice. Based on the analysis of the data obtained the average results of the experimental class post-test 78.95 and the average post-test control class 71.50. Hypothesis test results using t-test (Polled Variance) obtained t_count = 2.361 while (dk = 24 + 22 - 2 = 44) with a 5% significance level obtained t_table = 2.020, which means tcount> t table, then  accepted, this proves that there is an effect of the application of the Example Non Example model on Thematic Student learning outcomes. Based on the results of the calculation of Effect Size (ES) obtained ES = 0.73 including medium criteria.Keywords : Influence, Learning Outcomes, Model Example Non Example, Thematic Learning.